An explicit multi-phase field damage model for long fiber-reinforced composites. (1st April 2023) - Zou, Xiaocan; Xu, Zhonghai; Gao, Jin; Wu, Shibao; Li, Ruoyu; Li, Wenjie; He, Xiaodong
Abstract: In this paper, a novel explicit multi-phase damage model based on the puck failure criterion and explicit dynamics is proposed to predict the progressive failure process of composite laminates. Further, a model penalty parameter is introduced to reformulate the crack surface energy density for different failure modes to ensure reasonable damage prediction results. The model has undergone rigorous algebraic derivation to ensure thermodynamic consistency. Finally, the effects of explicit multi-phase field parameters on the damage prediction of composite are investigated by two representative cases, the results show that the phenomenological failure criteria combined with appropriate explicit multi-phase field parameters can reasonably explain the progressive failure process of composite laminates.